Reduction in the cerebrospinal fluid protein level after bevacizumab treatment in patients with optic pathway low‐grade gliomas. Issue 5 (2nd March 2022) - da Costa, Marcos Devanir; Watanabe, Rodrigo Akira; Soares, Carolina Torres; Dassi, Natalia; Dastoli, Patricia Alessandra; Nicácio, Jardel Mendonça; Cappellano, Andrea Maria; Silva, Nasjla Saba; Cavalheiro, Sergio
Abstract: Optic pathway gliomas (OPG) can cause elevated cerebrospinal fluid (CSF) protein concentrations. We report on two patients with suprasellar low‐grade gliomas and high CSF protein levels (590 and 551 mg/dl) that precluded shunt implantation. After two and three doses of bevacizumab, respectively, the levels dropped dramatically to 191 and 178 mg/dl, respectively. Bevacizumab treatment was associated with a decrease in CSF protein level, allowing successful shunt placement. Our results are consistent with the pharmacological mechanism of bevacizumab, which decreases protein leakage from blood vessels to the ventricles.